2020
DOI: 10.1186/s12866-020-01782-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation of murine RAW264.7 macrophages by sonicated and alkalized paramylon from Euglena gracilis

Abstract: Background Euglena is a new super health food resource that is rich in the natural polysaccharide paramylon, a linear β-1,3-glucan with various biological activities including activity on the immune system in different cell lines and animals. Despite these reports, the immune regulation mechanism of paramylon is still unclear. Results We investigate the signaling pathways paramylon impacts in immune macrophages. In RAW264.7 macrophag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…The total algal chlorophyll was extracted with 95% ethanol, and the content was spectrophotometrically assayed according to the method (Harris, 2009;Smith, 2009). The paramylon of 5 × 10 7 -10 8 cells was extracted and measured as described previously (Sugiyama et al, 2009;Nakazawa et al, 2017;Guo et al, 2020). The total lipids of 10 7 -10 8 cells were measured using the oven-drying method (Yang et al, 2018).…”
Section: Cultivation and Stress Treatmentsmentioning
confidence: 99%
“…The total algal chlorophyll was extracted with 95% ethanol, and the content was spectrophotometrically assayed according to the method (Harris, 2009;Smith, 2009). The paramylon of 5 × 10 7 -10 8 cells was extracted and measured as described previously (Sugiyama et al, 2009;Nakazawa et al, 2017;Guo et al, 2020). The total lipids of 10 7 -10 8 cells were measured using the oven-drying method (Yang et al, 2018).…”
Section: Cultivation and Stress Treatmentsmentioning
confidence: 99%
“…Based on this, paramylon is already marketed as an immunostimulatory agent in nutraceuticals. Beta-glucan from Euglena algae is a new immune-support ingredient, as the naturally occurring beta-glucan content is recognized explicitly by immune cell receptors [88]. Preclinical and clinical studies support the positive effects of this microalga and its beta-glucan content on multiple aspects of immunity [87].…”
Section: Beta-glucanmentioning
confidence: 99%
“…These soluble nanofibers have been shown to enhance stimulation of leucocytes and hepatoprotection because of the formation of more bioactive single helices (Kusumic et al, 2018). In a recent study, alkali treated paramylon has been shown to activate the immuneresponse in murine RAW264.7 cells (Guo et al, 2020). The SEM of soluble paramylon clearly depicts the opening of the paramylon granules (Figure 3).…”
Section: Prebiotic Activity Of E Gracilis Cell Extract and Sds Extracted Paramylonmentioning
confidence: 87%
“…The paramylon itself is a recalcitrant substrate, however different pretreatment methods have been reported to obtain soluble β-1, 3-glucans (Gissibl et al, 2018, Kusumic et al, 2018. The paramylon treatment with sodium hydroxide is known to reduce the degree of polymerization J o u r n a l P r e -p r o o f (Guo et al, 2020) and also yield soluble nanofibers (Katoka et al, 2002). These soluble nanofibers have been shown to enhance stimulation of leucocytes and hepatoprotection because of the formation of more bioactive single helices (Kusumic et al, 2018).…”
Section: Prebiotic Activity Of E Gracilis Cell Extract and Sds Extracted Paramylonmentioning
confidence: 99%